Creativity of Arabic Language Education Students in Designing Teaching Materials: A Project-Based Approach in the Tathwir Mawaad Course for ALF Learners - Hayati, Salma; Lailatussaadah, Lailatussaadah; Rizki, Aulia (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
The teaching materials for Arabic used in formal educational institutions for Arabic Language Foreign (ALF) students are typically in the form of textbooks that have been predetermined and have not been supplemented with additional materials designed according to current needs and contexts. The purpose of this study is to analyze the creativity of Arabic students in designing teaching materials to be used in Arabic language learning at educational institutions for ALF and to describe the learning process of the course Tathwir Mawaad li Al-Lughah Al-Arabiyah based on an outcome approach. This study employed a qualitative descriptive method, analyzing 120 student project outcomes and conducting interviews with 7 participants.The results of the study show that Arabic students possess creativity in designing Arabic teaching materials in both digital and non-digital formats. This creativity is strongly supported by the learning process carried out by the course instructors of Tathwir Mawaad li Al-Lughah Al-Arabiyyah through Project-Based Learning (PjBL). The Tathwir Mawaad li Al-Lughah Al-Arabiyyah course in the Arabic Language Education Program at UIN Ar-Raniry has successfully guided students to develop creativity in designing diverse Arabic teaching materials suited to contemporary contexts for use by ALF in educational institutions. This study contributes to the development of an outcome-based curriculum and provides insights for enhancing Arabic language teacher training programs, particularly in fostering creativity and contextual material design.